2016
DOI: 10.1103/physrevd.94.063532
|View full text |Cite
|
Sign up to set email alerts
|

New perturbative method for analytical solutions in single-field models of inflation

Abstract: We propose a new parametrization of the background equations of motion corresponding to (canonical) single-field models of inflation, which allows a better understanding of the general properties of the solutions and of the corresponding predictions in the inflationary observables. Based on the tools of dynamical systems, the method suggests that inflation comes in two flavors: power-law and de Sitter. Power-law inflation seems to occur for a restricted type of potentials, whereas de Sitter inflation has a muc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…To briefly illustrate the difference with respect to the dynamical ones, let us consider the well known example in Class Ia which is the quadratic potential V (φ) = (m 2 φ /2)φ 2 (A = 0, B = m φ / √ 2 and α 2 = 0), where m φ is the mass of the scalar field [40]. It can be shown that for this case y 1i = 2 √ 2B/H i = 2m φ /H i , where H i is the initial value of the Hubble parameter (see also Sec.…”
Section: Refmentioning
confidence: 99%
See 1 more Smart Citation
“…To briefly illustrate the difference with respect to the dynamical ones, let us consider the well known example in Class Ia which is the quadratic potential V (φ) = (m 2 φ /2)φ 2 (A = 0, B = m φ / √ 2 and α 2 = 0), where m φ is the mass of the scalar field [40]. It can be shown that for this case y 1i = 2 √ 2B/H i = 2m φ /H i , where H i is the initial value of the Hubble parameter (see also Sec.…”
Section: Refmentioning
confidence: 99%
“…[22]. The particular, polar form of the transformation into a dynamical system which we use in this work was first proposed for dark matter models and the inflationary scenario in [39,40], but see also [41,42] for other related works. As mentioned above, we shall show that there is a general parametrization from which almost all the popular quintessence potentials can be derived.…”
Section: Introductionmentioning
confidence: 99%
“…The scalar field energy density and pressure are given by the canonical expressions ρ φ = (1/2)φ 2 + V (φ) and p φ = (1/2)φ 2 − V (φ). We define a new set of polar coordinates as in [28,45,46],…”
Section: Background Dynamicsmentioning
confidence: 99%
“…(40) can be written in the form of (26) under the simple change of variable ω = 3 n 0 ln (ω). The same transformation can be applied in the master equation, (45), which is transformed into equation (40). Moreover, if we also apply the transformation (78) to (45), then the latter takes the form of the master equation, (26).…”
Section: Equivalent Transformationsmentioning
confidence: 99%
“…In [31][32][33][34][35][36][37], the perturbative reconstruction approach was applied: the inflaton self-interaction potential, V (φ), of the scalar field, φ, was reconstructed by considering a series expansion around a point φ = φ 0 , where the coefficients of the series expansion for the potentials are determined from the observable values of the scalar spectral index and the usual slow-roll parameters; for more details see [38]. Alternative approaches to the reconstruction of the scalar field potential include a stochastic perturbative approach in [39], or another perturbative approach in [40]. Two alternative methods for the reconstruction of the scalar field potential have been proposed in [41] and [42].…”
Section: Introductionmentioning
confidence: 99%